(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2015)
The article reports part of the results of a research on the presence of the Russian mafia in Italy, conducted in 2013 and grounded on investigative and judiciary sources (at the moment the research is undergoing an update). After addressing the definition’s problems posed by the "Russian mafia" locution, the article focuses on the invisibility of illicit money coming from the countries of the former Soviet Union, whose traces, well present in Italy, are not sufficient to prove the crime of money laundering, which requires the identification of the crime that generated the money. Afterwards, it deals with the Georgian component of the Russian mafia, reconstructing the characteristics and criminal activities carried out in Italy by the members of the last level of the organization. Finally, the article looks at the Ukrainian variant of the Russian mafia, which is involved into racketeering, smuggling human beings and exploitation of prostitution (crimes committed against compatriots), and it reads it through the model of quasi-rooting. In the conclusions it is argued that the development of the criminal organizations, that can be inserted within the Russian mafia present in Italy, is characterized by traits that show a typically mafia orientation and at the same time cannot allow to read the phenomenon as a process of colonization, unlike the Italian mafias’s move in new territories.